Roslyn Rutabaga and the biggest hole on earth - Gay, Marie-Louise (Groundwood Books ; House of Anansi Press, 2010)
Roslyn Rutabaga is a rabbit. One day she has a plan to dig the biggest whole on earth. Will she succeed?